Relationship between health literacy and self care management in people with type 2 diabetes mellitus in Indonesia - A. Sabil, Fitri; Anisa, Nurul Rezki (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
Health literacy is considered one of the influencing factors to self-care management in people with type 2 Diabetes Mellitus. American Diabetes Association stated that complications in people with type 2 diabetes mellitus tend to increase and get worse due to the inability to manage the disease independently. This study aimed to determine the relationship between health literacy and self-care management in the Health Centers in Makassar City. Measurements using the HLS-Q16 instrument for health literacy and diabetes self-management questionnaire (DSMQ) for self-care management. Data was analyzed by using fisher’s exact test. The results showed an adequate level of health literacy with 71 respondents and a low level of self-care management with 74 respondents from 126 respondents and there was a relationship between health literacy and self-care management with p-value = 0.004 <0.05. These findings can be additional information material to design programs and training that support the improvement